2022
DOI: 10.1071/cp21598
|View full text |Cite
|
Sign up to set email alerts
|

Growth, metal partitioning and antioxidant enzyme activities of mung beans as influenced by zinc oxide nanoparticles under cadmium stress

Abstract: Context Cadmium (Cd) toxicity and zinc (Zn) deficiency are of major concerns for crop growth and quality. Moreover, their interactive effects exert some controversial reports. Aims The effects of zinc oxide nanoparticles (ZnO NPs) and Cd on growth, physiology, and metal distribution in mung beans (Vigna radiata L.) was investigated. Methods Seven-day-old seedlings were treated with Zn (0, 1, 2, 4, 8, 16 and 32 μM) and Cd (0, 0.5, 1 μM) for 14 days. Key results Photosynthetic pigments, antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…(2018) showed that growing wheat in selenium-rich soil reduces the content of toxic metals such as Ni and Pb in roots and shoots. Zinc oxide (ZnO) nanoparticles prevented the adverse effects of cadmium stress in the plant but caused the accumulation of Cd in the root and stem tissues of mung beans ( Rashid et al., 2022 ).…”
Section: Application Of Selenium and Zinc For Crop Biofortificationmentioning
confidence: 99%
“…(2018) showed that growing wheat in selenium-rich soil reduces the content of toxic metals such as Ni and Pb in roots and shoots. Zinc oxide (ZnO) nanoparticles prevented the adverse effects of cadmium stress in the plant but caused the accumulation of Cd in the root and stem tissues of mung beans ( Rashid et al., 2022 ).…”
Section: Application Of Selenium and Zinc For Crop Biofortificationmentioning
confidence: 99%
“…Antioxidant enzymes were upregulated by ZnO NPs in order to prevent oxidative stress and preserve growth performance. (Rashid et al, 2022) ZnO nanoparticles decreased carotenoid contents in maize leaves Chlorophylls, proteins, DNA, and lipids are among the cellular constituents that carotenoids are crucial in preventing oxidative damage to and capturing radical oxygen species. (Hashemi et al, 2019) One of the most frequent stress responses to heavy metal exposure in plants is the production of reactive oxygen species (ROS), which can alter metabolism through oxidative cell damage (Venkatachalam et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles are found to be very toxic to different plant species [46], while they play a crucial role in promoting plant growth in others [47,48]. Zinc is known to be involved in controlling enzymes, protein synthesis, cell elongation, regulating membrane function, and increasing plant tolerance to environmental stress [49], and high Zn content in seeds could act as a seed germination starter and promote early seedling growth by speeding up metabolism [50][51][52]. Muhammad et al [53] demonstrated that ZnO nanoparticle priming increased Zn content in maize seed embryo tissues and aleurone layers.…”
Section: Discussionmentioning
confidence: 99%